Longitudinal trends of high school physics students’ perceptions of experience, difficulty, and development in a long-term inquiry framework - Michal Sigron; Dorothy Langley; Stanisław Dylak; Edit Yerushalmi (Physical Review Physics Education Research)
Response to the continuing call to integrate scientific inquiry activities into high school education has taken different forms varying in student ownership, physical setting, time span, and mentoring resources. Important issues are how students perceive central dimensions of their experience, and the extent to which the inquiry framework design serves to promote a sense of growth in the participants. The current research followed a group of 34 high school physics students who participated in the out-of-school Research Physics program over a 3-year period (2016–2019), gradually progressing from inquiry-oriented lab activities to an extended inquiry project under the guidance of teacher-mentors, within an instructional design of cognitive apprenticeship. The research focused on a set of 15 inquiry components, some directly related to experimental practices such as formulating inquiry questions, preparing and performing experiments, data processing using technological tools, others related to the scientific culture of presenting oral and written inquiry reports, and finally abilities of teamwork and self-regulation. Data regarding students’ perceptions of three aspects—Experience, Difficulty, and Development with respect to the inquiry components, were collected at the end of each year, using self-report questionnaires. The analysis of longitudinal trends revealed several inquiry components for which significant changes occurred in the perceptions of the three aspects, which can be mainly related to the program design. The research hypothesis regarding the relationship between the three aspects was that the perceived Development would match the levels of the perceived Experience and Difficulty for all 15 inquiry components. The quantitative analysis revealed four groups of inquiry components, only two of which aligned with the hypothesis. The quantitative findings are explained based on program design and qualitative data about student effort and ways of coping and teacher-mentor scaffolding methods.